ERYTHRODERMIC PSORIASIS IN ADULT MALE PATIENT TREATED WITH SYSTEMIC CORTICOSTEROID : A CASE REPORT - Prayogi Miura Susanto (Universitas Pahlawan Tuanku Tambusai, 2022)
Erythroderma is a severe skin disorder that requires immediate and adequate treatment. The most common cause of erythroderma, which can be detrimental to the patient's life, is psoriasis. We describe a case of erythroderma psoriasis (EP) in a 57-year-old male patient without underlying systemic disease. The patient was diagnosed based on his medical history and physical examination. The management is interdisciplinary and comprehensive. Patients' clinical outcomes improved significantly after receiving topical and systemic corticosteroids.